Pengaruh Model Pembelajaran Kooperatif Two Stay Two Stray (TSTS) Berbantuan Media Interaktif Berbasis STEM Terhadap Berpikir Kritis dan Hasil Belajar Siswa Pada Materi Sistem Indera Di SMA Negeri 2 Kerinci - Eria Marina Sepriyani; Lufri; Irdawati; Yuni Ahda (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of the two-stay two stray cooperative learning model (TSTS) assisted by STEM-based interactive media on critical thinking and student learning outcomes on sensory system material at SMA Negeri 2 Kerinci. This type of research is quasi-experimental research with a randomized control-group posttest-only design. The population of this study came from class XI students of SMA Negeri 2 Kerinci for the 2021/2022 Academic Year. The sampling technique used is a purposive sampling technique, namely that the determination of the sample takes into account certain criteria that have been made for the subject according to the research objectives. Data analysis techniques used the normality test, homogeneity test, and hypothesis test. Based on the research that has been done, it can be concluded that the STEM-based two stay two stray learning model has an effect on critical thinking and student learning outcomes on sensory system material at SMA Negeri 2 Kerinci.